The Effect of Diamond Fraud on Indications of Financial Statement Fraud in Manufacturing Companies - Reni Dwi Widyastuti; Yolanda Bilivianty; Wilda Sari; Aris Setiawan (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Financial statement fraud remains a critical issue in the manufacturing sector, where complex operations and managerial discretion create opportunities for manipulation, highlighting the need to examine the roles of pressure, opportunity, rationalization, and capability as outlined in the fraud diamond framework. This research investigates the influence of the fraud diamond elements on the occurrence of financial statement fraud. Fraudulent financial reporting continues to pose a critical challenge for corporations, as inaccuracies reduce the reliability and usefulness of information in the decision-making process. Recognizing the underlying drivers of such fraud is therefore essential. The study employs a quantitative method and utilizes secondary data derived from annual reports. The research population comprises manufacturing firms listed on the Indonesia Stock Exchange between 2021 and 2023. Through purposive sampling, 39 firms were selected as the sample. Data analysis was conducted using logistic regression with the aid of EViews version 13. The findings reveal that rationalization and capability exert a significant influence on financial statement fraud, whereas pressure and opportunity show no significant effect. These results contribute empirical insights into the dominant determinants of financial reporting fraud and highlight implications for strengthening corporate governance and fraud detection practices in the Indonesian manufacturing industry.